Structure of the master regulator Rns reveals an inhibitor of enterotoxigenic Escherichia coli virulence regulons - Charles R. Midgett (Nature Portfolio, 2021)
Abstract Enteric infections caused by the gram-negative bacteria enterotoxigenic Escherichia coli (ETEC), Vibrio cholerae, Shigella flexneri, and Salmonella enterica are among the most common and affect billions of people each year. These bacteria control expression of virulence factors using a network of transcriptional regulators, some of which are modulated by small molecules as has been shown for ToxT, an AraC family member from V. cholerae. In ETEC the expression of many types of adhesive pili is dependent upon the AraC family member Rns. We present here the 3 Å crystal structure of Rns and show it closely resembles ToxT. Rns crystallized as a dimer via an interface similar to that observed in other dimeric AraC’s. Furthermore, the structure of Rns revealed the presence of a ligand, decanoic acid, that inhibits its activity in a manner similar to the fatty acid mediated inhibition observed for ToxT and the S. enterica homologue HilD. Together, these results support our hypothesis that fatty acids regulate virulence controlling AraC family members in a common manner across a number of enteric pathogens. Furthermore, for the first time this work identifies a small molecule capable of inhibiting the ETEC Rns regulon, providing a basis for development of therapeutics against this deadly human pathogen.